2021
DOI: 10.1016/j.jenvp.2021.101556
|View full text |Cite
|
Sign up to set email alerts
|

Does place visualisation increase household preparedness for natural hazard events? A longitudinal intervention

Abstract: Novel approaches are needed to increase preparedness behaviours in populations with high disaster risk. Crucially, such approaches need to take into account the relationships that people have with place. We report a randomised controlled trial to test the effectiveness of an online place attachment mental visualisation task to increase preparedness behaviours.Findings from a pilot (Study 1) using pre and post-test measures showed mixed evidence for the influence of mental visualisation on place attachment. Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Greater knowledge of how place attachment is associated with different types of preparedness provides greater confidence in the impact of any evidencebased intervention that may be trialed moving forward. One example of how this could be approached is through facilitating the active awareness of peoples' attachments to their houses and neighborhoods as a means of increasing preparedness (e.g., Wallis et al, 2021). More broadly, this research also gives added significance to the role of place attachment in explaining behavior (i.e., through mediating the length of residence and home ownership to preparedness link).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Greater knowledge of how place attachment is associated with different types of preparedness provides greater confidence in the impact of any evidencebased intervention that may be trialed moving forward. One example of how this could be approached is through facilitating the active awareness of peoples' attachments to their houses and neighborhoods as a means of increasing preparedness (e.g., Wallis et al, 2021). More broadly, this research also gives added significance to the role of place attachment in explaining behavior (i.e., through mediating the length of residence and home ownership to preparedness link).…”
Section: Discussionmentioning
confidence: 96%
“…In line with this emphasis on greater precision, rather than treating "disaster preparedness" as one behavioral category, the second aim of our research is to understand the extent to which place attachment is associated with different types of preparedness (e.g., Spittal et al, 2008). We differentiate between survival, mitigation, and community behaviors (for a similar approach see Wallis et al, 2021). Survival behaviors, for instance, directly contribute to the safety and wellness of individuals once a natural hazard event has occurred (e.g., storing food and water).…”
Section: Preparedness and Spatial Scales Of Attachmentmentioning
confidence: 99%
“…It also has an influence on their perceptions of climate change, and may increase the intention of adopting adaptive behaviours. However, studies have typically only focused on linkages to residential places, and it is probable that place identity for recreational spaces (e.g., natural spaces) is also relevant in understanding disaster prevention behaviours [55]. Further studies should consider this aspect, as well as exploring how the perceptions of life impact experiences influence perceived control and how this relates to coping strategies, including the role that place identity has in the perception of control.…”
Section: Discussionmentioning
confidence: 99%
“…There is mixed evidence to date on the utility of visualisation techniques in place attachment research. Wallis et al. (2021) found that mental visualisations of disaster did not have the anticipated effect of increasing mitigation or preparedness behaviours.…”
Section: Introductionmentioning
confidence: 93%